The Relevance of Ibn Khaldun's Educational Methods to Contemporary Education - Afrina Rambe, Anggi; Syahidin, Syahidin; Supriadi, Udin; Fakhruddin, Agus; Bujang, Bujang; Maswar, Rezi; Rasyid, Ahmad (STIT Ahlussunnah Bukittinggi, 2024)
The increasingly developing pattern of education certainly cannot be separated from the thoughts of Islamic figures, one of whom is Ibnu Khaldun, who contributed his thoughts to the development of education. This research aims to analyze the relevance of Ibn Khaldun's educational methods to contemporary education, especially Islamic religious education. This research uses a qualitative method with a library approach, data sources are taken from several books, journals, articles, and writings related to the research problem being studied so that the data obtained is more accurate. The results of research on the educational methods proposed by Ibnu Khaldun show that eight methods are suitable for current educational methods that can still be applied to contemporary education, namely; 1) Tadarruj, 2) Tikrari, 3) Alqrub wa Almuyana, 4) Determining maturity in learning, 5) Physical and psychological adaptation, 6) Potential development, 7) Mastery of one field of knowledge, 8) Widya Wisata, 9) Tadrib, and 10) Book Summarization. Based on these findings, Ibnu Khaldun's thoughts are still used in contemporary education because suitability in the world of education cannot be separated from the methods and creativity of educators, and Ibnu Khaldun's thought methods are also still relevant to education in this modern era.